The Gap Between the Goals of Physical Education and the Reality of Its Practice in MI Walisongo Semarang - Rouf, Abdur; Pitaloka, Diah Ayu; Pathurrohman, Pathurrohman (Yayasan Insan Mulia Bima, 2026)
This study aims to explore the gap between the ideal goals of physical education in the curriculum and its actual practice at MI Walisongo Semarang. This issue is crucial since physical education in Islamic elementary schools often faces limitations in facilities, time allocation, and teacher competence. The research employed a qualitative approach with an intrinsic case study design, involving a physical education teacher, the school principal, and students as participants. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal three main themes: (1) teachers’ adaptive practices amid limited resources, (2) reflective understanding of the goals of physical education, and (3) the integration of Islamic values within physical activities. Despite not having a sports education background, the teacher demonstrated creativity through modified tools, game-based learning, and contextual teaching strategies. Physical education activities not only fostered physical fitness but also strengthened students’ character and spirituality. The results reinforce Bourdieu’s theory of social practice regarding the interplay between agency and structure in education. Practically, this study highlights the importance of continuous professional development for non-specialist PE teachers and institutional support to enhance value-based physical education in Islamic schools. This study offers a unique contribution by depicting the dynamics of learning from the perspective of the non-linear teacher, which is the primary focus. Academically, the results of this research open up new discussion about adaptive pedagogy in the context of Islamic education with structural constraints.